Recalcitrant Epithelial Ingrowth After LASIK: An Unexpected Complication: Poster Presentation - Case Report - Resident - Putri Pamulani; Angga Fajriansyah; Elfa Ali Idrus; Patriotika Muslima; Arief Akhdestira Mustaram (Majalah Oftalmologi Indonesia, 2023)
Introduction : Post-LASIK Epithelial Ingrowth (PLEI) is an uncommon complication of laser in situ keratomileusis (LASIK). Treatment for PLEI can be done surgically and medically, but recurrence is possible. Case Illustration : A 20-year-old female came with the appearance of white opacity on her right cornea, which has grown bigger in size over the last two months (Figure 1A and 1B). She had undergone three debridement surgeries prior to the visit due to the same complaint and history of LASIK surgery two years before. Visual acuity of the right eye showed 0.32 pinhole 0.63, epithelial ingrowth Probst/Machat grade III in 9 o’clock direction approximately 3mm x 3mm (Table 1), pooling on fluorescein test, intact flap, and punctate epithelial erosion (PEE). A surgery of flap reopening, epithelial debridement, corneal suture, and corneal crosslinking was conducted (Figure 2 and 3). Discussion : The incidence of PLEI, as reported by published studies, is relatively low. Hence, treatment in such cases is largely based on anecdotal case reports and small case series. Treatment of choice can be done according to clinical manifestation and severity of PLEI. Conclusion : A thorough and careful management of PLEI should be carried out to prevent its progress and recurrence.